INDEPENDENT LEARNING STRATEGY OF NATURAL SCIENCE WITH “ONE DAY ONE DIARY FOR SCIENCE” PROGRAM (Department of Physics, Faculty of Mathematics and Natural Sciences, 2015)
Learning behavior and metacognitive skill of students affect cognitive value and level of understanding of each student. The application of the